Endoscopic treatment of ureterocele in children: Results of a single referral tertiary center over a 10 year-period. Issue 2 (April 2022) - Pani, Elisa; Negri, Elisa; Cini, Chiara; Landi, Luca; Mantovani, Alberto; Bortot, Giulia; Masieri, Lorenzo
Summary: Introduction: The management of UCs remain controversial, especially for UCs with duplex collecting systems that still represent a great challenge in paediatric urology. Several approaches have been used and a shared management is not yet validated. Study aim: Aim of our study is to evaluate the results of the endoscopic treatment of UC comparing ortothopic single-system UC and ectopic duplex-system UC over a 10-year period in a single referral tertiary center. Success was defined as resolution of dilation, lack of urinary infections and preservation of renal function. Study design: We retrospectively reviewed medical records of children with a diagnosis of UC who underwent endoscopic puncture at our division from January 2009 to January 2019. Patients were divided in two groups: Group A composed of patients with ectopic UC associated with renal duplex system and Group B with orthotopic UC in single collecting system. Results: We identified 48 paediatric patients treated with transurethral primary endoscopic incision. Groups result homogeneous for clinical and pathological characteristics. The only statistical significative difference between the two samples was the age at diagnosis (p value with Yates correction = 0.01) . Discussion: We considered as a therapeutic success infections control and the elimination of obstruction with preservation of global kidney function. Based on that, our success rate after single (77%) or double (92%) endoscopic treatment is higher than data reported in literature. Differently from previous studies, vescico-ureteral reflux without UTIs was not considered as a failure of the procedure. The present study has some limitations: it is a retrospective and monocentric serie and it lacked a longer follow-up; on the other hand, it has been conducted on a quite large sample size and it is one of the few studies that compares the endoscopic treatment between orthotopic and ectopic UC. Conclusion: Our data report primary endoscopic puncture of ureterocele as a simple, effective, and safe procedure also in long-term follow up. This technique avoids the need for additional surgery in the majority of the patients, also in the case of an ectopic UC associated to a duplex system. Summary Table Post treatment data were summarized in Table 3 . Summary Table Persistent UTIs Persistent VUR "De Novo" VUR UC sac bulging requiring second look Group A 11 (42.3%) 1 (3.8%) 5 (19.2%) 6∗ (23.1%) Group B 4 (18.2%) 1 (4.5%) 0 (0%) 2 (9.1%) P Value (Yates correction) 0.14 0.54 0.09 0.36